Local impedance and contact force guidance to predict successful cavotricuspid isthmus ablation with a zero-fluoroscopy approach - Melero-Polo, Jorge; Cabrera-Ramos, Mercedes; Alfonso-Almazán, Jose Manuel; Marín-García, Isabel; Montilla-Padilla, Isabel; Ruiz-Arroyo, José Ramón; López-Rodríguez, Guillermo; Ramos-Maqueda, Javier (Frontiers in Cardiovascular Medicine, 2024)
Introduction A new technology capable of monitoring local impedance (LI) and contact force (CF) has recently been developed. At the same time, there is growing concern regarding catheter ablation performed under fluoroscopy guidance, due to its harmful effects for both patients and practitioners. The aim of this study was to assess the safety and effectiveness of zero-fluoroscopy cavotricuspid isthmus (CTI) ablation monitoring LI drop and CF as well as to elucidate if these parameters can predict successful radiofrequency (RF) applications in CTI ablation. Methods We conducted a prospective observational study recruiting 50 consecutive patients who underwent CTI ablation. A zero-fluoroscopy approach guided by the combination of LI drop and CF was performed. In each RF application, CF and LI drop were monitored. A 6-month follow-up visit was scheduled to assess recurrences. Results A total of 767 first-pass RF applications were evaluated in 50 patients. First-pass effective RF applications were associated with greater LI drops: absolute LI drops (30.05 ± 6.23 Ω vs. 25.01 ± 5.95 Ω), p = 0.004) and relative LI drops (−23.3 ± 4.9% vs. −18.3 ± 5.6%, p = 0.0005). RF applications with a CF between 5 and 15 grams achieved a higher LI drop compared to those with a CF below 5 grams (29.4 ± 8.76 Ω vs. 24.8 ± 8.18 Ω, p < 0.0003). However, there were no significant differences in LI drop between RF applications with a CF between 5 and 15 grams and those with a CF beyond 15 grams (29.4 ± 8.76 Ω vs. 31.2 ± 9.81 Ω, p = 0.19). CF by itself, without considering LI drop, did not predict effective RF applications (12.3 ± 7.54 g vs. 11.18 ± 5.18 g, p = 0.545). Successful CTI ablation guided by a zero-fluoroscopy approach was achieved in all patients. Only one patient experienced a recurrence during the 6-month follow-up. Conclusions LI drop (absolute and relative values) appears to be a good predictor of successful RF applications to achieve CTI conduction block. The optimal CF to achieve a good LI drop is between 5 and 15 g. A zero-fluoroscopy approach guided by LI and CF was feasible, effective, and safe.